Meningkatkan Hasil Belajar Siswa tentang Zakat melalui Metode Multiple Styles Berbasis TPACK di SDN Mlatiharjo 02 - Zahrotunnayyiroh, Zahrotunnayyiroh (Jurnal Didaktika Pendidikan Dasar, 2024)
Boredom Boredom will affect the enthusiasm and learning outcomes of students in zakat material so that they do not reach CP (learning achievement). Children’s difficulties in understanding zakat material provide a challenge for researchers always to try to create learning innovations that are fun and meaningful. One solution that can overcome this problem is by applying 3 methods in one lesson which English terms can be called Multiple Styles, which means various methods. Can the use of the TPACK-based Multiple Styles method improve student learning outcames? This research aims to obtain meaningful and appropriate learning using the Multiple Styles method and determine the improvement in student learning outcomes. This reaserch uses the Classroom Action Research method which consists of 3 cycles. This research was carried out in class IV of Mlatiharjo 02 School, consisting of 28 students. The results of the research showed that the average result of cycle 1 was 70%, after carrying out cycle 2 the value inscreased to 83%, while in cycle 3 the achievement reached 98%. The conclusion of this research was that student learning outcomes regarding zakat by combining 3 methods or Multiple Styles were successful.